Preparation method of PBAT composite material with controllable natural environment biodegradation rate

By wrapping PA4 with degradation regulator into microcapsules and compounding with PBAT, the problem of the difference in degradation rate of PBAT agricultural mulch in different regions is solved, and the controllability of the degradation rate and the guarantee of material performance is achieved.

CN119752130AInactive Publication Date: 2025-04-04SHANGHAI SUNNY NEW TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411980868.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The environmental degradation rate of existing PBAT agricultural mulch varies greatly in different regions and cannot be effectively degraded in drought or low-fertility areas. However, the degradation in warm and humid environments leads to damage to the mulch.

Method used

By wrapping polybutyracam (PA4) with degradation regulator into microcapsules and compounding with PBAT, hydrogen bond receptor-type activator promotes the dissolution and dispersion of PA4, PBAT composite materials with controllable biodegradation rate in the natural environment were prepared.

Benefits of technology

It realizes the degradation rate regulation of PBAT in different environments, ensures the thermal processing performance and service life of the material, and expands the application of PA4.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a PBAT composite material with a controllable natural environment biodegradation rate, which comprises the following steps: dispersing PA4, a hydrogen bond receptor type activator and a degradation regulator in a solvent, stirring at a high speed of 1000-2000r / min to evaporate the solvent, condensing the PA4 in the solvent evaporation process and separating out the PA4 on the degradation regulator; the preparation method comprises the following steps: preparing a biodegradable microcapsule with PA4 as a shell and a degradation regulator as a core material, and carrying out twin-screw extrusion granulation on the biodegradable microcapsule and PBAT to prepare the PBAT composite material. The microcapsule modified PBAT with PA4 as a shell and a degradation regulator as a core material is used, the service life and the hot working performance of the PBAT can be guaranteed while the degradation rate of the PBAT in different environments can be controlled in a slow release mode, and the problem that the degradation rate of the PBAT is uncontrollable in the field of film packaging, especially when agricultural mulching films are applied to different regional environments is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer modified materials and relates to a method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment. Background Art

[0002] Polybutylene terephthalate adipate (PBAT) is widely used in agricultural mulch and food packaging due to its biodegradability and excellent ductility. However, in recent years, PBAT agricultural mulch has shown large differences in degradation rates in tests in different regions across the country. It cannot be effectively degraded in relatively arid areas or environments with low soil fertility, while in the warm and humid environment in the south, the mulch is prone to damage due to rapid degradation. If you try to directly add biodegradable components to the PBAT system, it is easy to cause PBAT degradation during thermal processing or affect its storage and transportation.

[0003] At present, there are related existing technologies that attempt to solve the problem of controlled degradation of PBAT mulch. For example, patent CN117964926A involves a controlled degradation mulch preparation and method thereof. The patent directly adds reducing dyes such as indigo and sprays reducing agents to allow leuco-sodium salt to enter the soil to etch the mulch. However, the patent mainly focuses on color degradation and does not involve controlled degradation of microcapsules.

[0004] Patent CN115946422B involves a PBAT-based biodegradable mulch film with controllable degradation. However, this patent achieves controlled degradation through multi-layer composite film formation of PBAT and starch, and does not involve controlled degradation of microcapsules.

[0005] The controlled degradation of microcapsules can realize the regulation of the degradation rate of PBAT in different soil environments without affecting the processing performance and mechanical properties of the material itself.

[0006] Therefore, it is of great significance to study a method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment to solve the problems existing in the prior art. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a method for preparing a PBAT composite material with a controllable biodegradation rate in a natural environment.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment comprises the following steps: firstly dispersing PA4 (polybutyrolactam), a hydrogen bond receptor type activator and a degradation regulator in a solvent, and evaporating the solvent by high-speed stirring at a rotation speed of 1000 to 2000 r / min; during the evaporation of the solvent, PA4 condenses and precipitates on the degradation regulator to form a biodegradable microcapsule with PA4 as a shell and the degradation regulator as a core material; and then granulating the biodegradable microcapsule and PBAT by twin-screw extrusion to obtain a PBAT composite material with controllable biodegradation rate in a natural environment.

[0010] As the preferred technical solution:

[0011] As described above, in the preparation method of a PBAT composite material with controllable biodegradation rate in a natural environment, the hydrogen bond receptor type activators are choline chloride and urea, choline chloride and urea are receptors that can bind to free hydrogen bonds with polybutyrolactam, and such receptors can be dispersed in common solvents to promote the dissolution of polybutyrolactam; the solvent is trichlorinated toluene and N,N-dimethylformamide, and the mass ratio of trichlorinated toluene and N,N-dimethylformamide is 1:1.

[0012] In the method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment as described above, the particle size of the biodegradable microcapsules is 10 to 30 μm.

[0013] As described above, in the preparation method of a PBAT composite material with controllable biodegradation rate in a natural environment, the melting point of PA4 is 260-270°C, and the number average molecular weight is 6000-8000 g / mol.

[0014] As described above, in the preparation method of a PBAT composite material with controllable biodegradation rate in a natural environment, the degradation regulator is a pro-degradation regulator or an anti-degradation regulator; the pro-degradation regulator is ethylenediamine, polyester hydrolase and probacterial agent, and the anti-degradation regulator is an antibacterial agent. These degradation regulators have a regulating degradation effect on biodegradable polyesters such as PBAT, but have little effect on the degradation of polybutyrolactam.

[0015] In the method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment as described above, the mass ratio of PA4, hydrogen bond receptor activator, degradation regulator and solvent is 3 to 6:0.5 to 2:3:100.

[0016] As described above, a method for preparing a PBAT composite material with a controllable biodegradation rate in a natural environment, wherein the shell thickness of the PBAT composite material with a controllable biodegradation rate in a natural environment is 5 to 20 μm.

[0017] According to the method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, the amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in a natural environment is 1 to 7 wt%.

[0018] In the method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment as described above, the extrusion temperature is 190 to 200°C.

[0019] Principle of the invention:

[0020] The present invention wraps the degradation regulator with polybutyrolactam (PA4) to prevent PBAT from contacting the degradation regulator, thereby ensuring the thermal processing performance and daily service life of PBAT; and the degradation rate of PBAT in different environments can be regulated by adjusting the thickness of the PA4 shell and the amount of microcapsules added, so as to achieve controlled degradation of microcapsules. PA4 is biodegradable and has good mechanical properties, but due to its high melting point (260-270°C), the thermal processing temperature is close to the decomposition temperature, and it is not suitable for preparing microcapsules by melt processing. At the same time, PA4 is difficult to dissolve and disperse in common organic solvents, which limits its application in solvent processing and molding. In order to solve the problem that PA4 is difficult to dissolve and disperse in solvents, it is difficult to prepare microcapsules by solvent evaporation. The present invention adds a hydrogen bond receptor activator, specifically receptors choline chloride and urea that can bind to free hydrogen bonds with PA4, and such receptors can be dispersed in common solvents, which promotes the dispersion of PA4 in the solvent, thereby finally preparing biodegradable microcapsules of a certain particle size by solvent evaporation.

[0021] Beneficial effects:

[0022] The present invention discloses a method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment. The method uses microcapsule-modified PBAT with PA4 as a shell and a degradation regulator as a core material. The method can slowly release and regulate the degradation rate of PBAT in different environments while ensuring its service life and thermal processing performance. The composite material solves the problem of uncontrollable degradation rate of PBAT in the field of film packaging, especially in the application of agricultural mulch in different regions, is conducive to its use and promotion, and expands the application of PA4. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0024] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0025] Degradation rate: The PBAT composite material was made into a 100 μm film sample. For Example 1 and Example 3, the sample was buried in the soil at a depth of 5 cm for 90 days at 20°C and 35% humidity, and a blank control group without the sample was set up to collect the carbon dioxide release of the system, and the degradation rate was calculated based on the carbon dioxide release. For Example 2 and Example 4, two samples were prepared, respectively, and recorded as Sample 1 and Sample 2, respectively. At 37°C and 70% humidity, Sample 1 was buried in the soil at a depth of 5 cm for 90 days, and a blank control group without the sample was set up to collect the carbon dioxide release of the system, and the degradation rate was calculated based on the carbon dioxide release. At the same time, Sample 2 was placed on the soil surface, and a blank control group without soil was set up, and the tensile strength retention rate was tested after 90 days.

[0026] Tensile strength: tested using a universal material testing machine with a tensile rate of 50 mm / min.

[0027] The sources of some substances of the present invention are as follows:

[0028] PBAT: TH805 from Lanshan Tunhe, Xinjiang Uygur Autonomous Region, commercially available.

[0029] Polyester hydrolase: Manufacturer: BASF, Brand: PHL-W7.

[0030] Ethylenediamine: commonly available on the market.

[0031] Beneficial bacterial agent: Manufacturer: Hubei Yijiajiu Biotechnology Co., Ltd., Brand: Microbial agent (fruit swelling and coloring).

[0032] Antibacterial agent: general-purpose tebuconazole antibacterial agent.

[0033] Example 1

[0034] A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, the specific steps are as follows:

[0035] (1) Preparation of raw materials:

[0036] PA4: melting point is 260-270°C, number average molecular weight is 6000-8000 g / mol;

[0037] Hydrogen bond acceptor activator: choline chloride and urea in a mass ratio of 1:1;

[0038] Degradation-promoting regulator: ethylenediamine, polyester hydrolase and probiotic agent in a mass ratio of 1:1:1;

[0039] Solvent: trichlorotoluene and N,N-dimethylformamide in a mass ratio of 1:1;

[0040] (2) dispersing PA4, a hydrogen bond acceptor type activator and a degradation promoter in a solvent, and evaporating the solvent by high-speed stirring at a speed of 1000 r / min. During the evaporation of the solvent, PA4 condenses and precipitates on the degradation promoter to form a biodegradable microcapsule with PA4 as a shell and the degradation promoter as a core material;

[0041] The mass ratio of PA4, hydrogen bond receptor activator, degradation regulator and solvent is 3:0.5:3:100; the average particle size of the biodegradable microcapsules is 30 μm;

[0042] (3) The biodegradable microcapsules and PBAT are granulated by twin-screw extrusion to obtain a PBAT composite material with controllable biodegradation rate in the natural environment; wherein the amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in the natural environment is 1wt%; the temperatures of each zone during twin-screw processing are: 180°C, 190°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 190°C.

[0043] The shell thickness of the finally obtained PBAT composite material with controllable natural environment biodegradation rate is 10 μm; the PBAT composite material with controllable natural environment biodegradation rate degrades in 90 days under 20°C and 35% humidity environment, and the degradation rate is 98% when buried at 5 cm.

[0044] Comparative Example 1

[0045] A method for preparing a PBAT composite material is basically the same as that of Example 1, except that the hydrogen bond acceptor type activator is omitted.

[0046] During the preparation process, PA4 is insoluble and difficult to disperse, and ultimately cannot be processed into a PBAT composite material.

[0047] By comparing Example 1 with Comparative Example 1, it can be seen that the hydrogen bond acceptor type activator of Example 1 can effectively promote the dissolution and dispersion of PA4, which is beneficial to the processing and molding of microcapsules. This is because the hydrogen bond acceptor type activator can bond with the free hydrogen bonds of PA4 and has good compatibility and dispersibility with the solvent, which can promote the dissolution and dispersion of PA4 in the solvent.

[0048] Example 2

[0049] A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, the specific steps are as follows:

[0050] (1) Preparation of raw materials:

[0051] PA4: melting point is 260-270°C, number average molecular weight is 6000-8000 g / mol;

[0052] Hydrogen bond acceptor activator: choline chloride and urea in a mass ratio of 1:1;

[0053] Degradation inhibitors: antibacterial agents;

[0054] Solvent: trichlorotoluene and N,N-dimethylformamide in a mass ratio of 1:1;

[0055] (2) dispersing PA4, a hydrogen bond acceptor type activator and an anti-degradation regulator in a solvent, and evaporating the solvent by high-speed stirring at a speed of 1300 r / min. During the evaporation of the solvent, PA4 condenses and precipitates on the anti-degradation regulator to form a biodegradable microcapsule with PA4 as a shell and the anti-degradation regulator as a core material;

[0056] The mass ratio of PA4, hydrogen bond receptor activator, degradation inhibitor and solvent is 3:0.5:3:100; the average particle size of the biodegradable microcapsules is 20 μm;

[0057] (3) The biodegradable microcapsules and PBAT are granulated by twin-screw extrusion to obtain a PBAT composite material with controllable biodegradation rate in the natural environment; wherein the amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in the natural environment is 3wt%; the temperatures of each zone during twin-screw processing are: 180°C, 190°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 190°C.

[0058] The shell thickness of the finally obtained PBAT composite material with controllable natural environment biodegradation rate is 10 μm; the PBAT composite material with controllable natural environment biodegradation rate degrades for 90 days under an environment of 37°C and 70% humidity, the degradation rate after burial of 5 cm is 99%, and the soil surface tensile strength retention rate is 85%.

[0059] Example 3

[0060] A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, the specific steps are as follows:

[0061] (1) Preparation of raw materials:

[0062] PA4: melting point is 260-270°C, number average molecular weight is 6000-8000 g / mol;

[0063] Hydrogen bond acceptor activator: choline chloride and urea in a mass ratio of 1:1;

[0064] Degradation-promoting regulator: ethylenediamine, polyester hydrolase and probiotic agent in a mass ratio of 1:1:1;

[0065] Solvent: trichlorotoluene and N,N-dimethylformamide in a mass ratio of 1:1;

[0066] (2) dispersing PA4, a hydrogen bond acceptor type activator and a degradation promoter in a solvent, and evaporating the solvent by high-speed stirring at a speed of 1600 r / min. During the evaporation of the solvent, PA4 condenses and precipitates on the degradation promoter to form a biodegradable microcapsule with PA4 as a shell and the degradation promoter as a core material;

[0067] The mass ratio of PA4, hydrogen bond receptor activator, degradation regulator and solvent is 6:2:3:100; the average particle size of the biodegradable microcapsules is 20 μm;

[0068] (3) The biodegradable microcapsules and PBAT are granulated by twin-screw extrusion to obtain a PBAT composite material with controllable biodegradation rate in the natural environment; wherein the amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in the natural environment is 5wt%; the temperatures of each zone during twin-screw processing are: 180°C, 190°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 190°C.

[0069] The shell thickness of the finally obtained PBAT composite material with controllable natural environment biodegradation rate is 20 μm; the PBAT composite material with controllable natural environment biodegradation rate degrades in 90 days under 20°C and 35% humidity environment, and the degradation rate is 97% when buried at 5 cm.

[0070] Example 4

[0071] A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, the specific steps are as follows:

[0072] (1) Preparation of raw materials:

[0073] PA4: melting point is 260-270°C, number average molecular weight is 6000-8000 g / mol;

[0074] Hydrogen bond acceptor activator: choline chloride and urea in a mass ratio of 1:1;

[0075] Degradation inhibitors: antibacterial agents;

[0076] Solvent: trichlorotoluene and N,N-dimethylformamide in a mass ratio of 1:1;

[0077] (2) dispersing PA4, a hydrogen bond acceptor type activator and an anti-degradation regulator in a solvent, and evaporating the solvent by high-speed stirring at a speed of 2000 r / min. During the evaporation of the solvent, PA4 condenses and precipitates on the anti-degradation regulator to form a biodegradable microcapsule with PA4 as a shell and the anti-degradation regulator as a core material;

[0078] The mass ratio of PA4, hydrogen bond receptor activator, degradation inhibitor and solvent is 6:2:3:100; the average particle size of biodegradable microcapsules is 15 μm;

[0079] (3) The biodegradable microcapsules and PBAT are granulated by twin-screw extrusion to obtain a PBAT composite material with controllable biodegradation rate in the natural environment; wherein the amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in the natural environment is 7wt%; the temperatures of each zone during twin-screw processing are: 180°C, 190°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 190°C.

[0080] The shell thickness of the finally obtained PBAT composite material with controllable natural environment biodegradation rate is 15 μm; the PBAT composite material with controllable natural environment biodegradation rate degrades for 90 days under an environment of 37°C and 70% humidity, the degradation rate after burial of 5 cm is 98%, and the soil surface tensile strength retention rate is 87%.

Claims

1. A method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment, characterized in that: First, PA4, a hydrogen bond acceptor type activator and a degradation regulator are dispersed in a solvent, and the solvent is evaporated by high-speed stirring at a speed of 1000-2000 r / min. During the evaporation of the solvent, PA4 condenses and precipitates on the degradation regulator to form biodegradable microcapsules with PA4 as a shell and the degradation regulator as a core material. The biodegradable microcapsules and PBAT are then granulated by twin-screw extrusion to obtain a PBAT composite material with a controllable biodegradation rate in the natural environment.

2. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The hydrogen bond acceptor type activators are choline chloride and urea, and the solvents are toluene trichloride and N,N-dimethylformamide.

3. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The particle size of the biodegradable microcapsules is 10 to 30 μm.

4. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The melting point of PA4 is 260-270°C, and the number average molecular weight is 6000-8000 g / mol.

5. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The degradation regulator is a degradation-promoting regulator or a degradation-inhibiting regulator.

6. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The mass ratio of PA4, hydrogen bond acceptor type activator, degradation regulator and solvent is 3-6:0.5-2:3:

100.

7. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 6, characterized in that: The shell thickness of the PBAT composite material with controllable biodegradation rate in the natural environment is 5 to 20 μm.

8. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The amount of biodegradable microcapsules added to the PBAT composite material with controllable biodegradation rate in the natural environment is 1 to 7 wt%.

9. The method for preparing a PBAT composite material with controllable biodegradation rate in a natural environment according to claim 1, characterized in that: The extrusion temperature is 190-200°C.

Citation Information

Patent Citations

  • Low-cost degradable plastic bag with adjustable degradation rate and preparation method thereof

    CN117186590A

  • Biodegradable microcapsules based on composite material and synthesis process

    US20240050916A1

  • KR20200047171A